2021
DOI: 10.1111/geb.13342
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche shifts in 815 introduced plant species affect their predicted distributions

Abstract: Aim Introduced species often occupy different climates in their introduced than their native range, but to what degree do such ‘climatic niche shifts’ interfere with our ability to predict invasions? Answering this question is crucial if we are to understand the threat invasive species pose to human and natural systems, especially given the ever increasing use of species distribution models as tools for invasive species risk assessment and management. Here we investigated the degree to which climatic niche shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Such a change in high-risk areas indicates that the niche shift of M. micrantha could cast uncertainty on its ENM-based risk assessment due to the colonization of novel climatic conditions in the IRSWC. These findings agree with the study by Atwater and Barney (2021) who showed that niche shifts greatly matter when modeling ecological niches of introduced species because they could significantly reduce the transferability of native-and introduced-range ENMs. Additionally, our results suggest the existence of a geographic separation of ranges and ongoing population expansion of M. micrantha in China, while Yang et al (2017) reported genetic differentiation of M. micrantha populations in the IRSWC and IRSC.…”
Section: Implications For Ias Managementsupporting
confidence: 92%
See 1 more Smart Citation
“…Such a change in high-risk areas indicates that the niche shift of M. micrantha could cast uncertainty on its ENM-based risk assessment due to the colonization of novel climatic conditions in the IRSWC. These findings agree with the study by Atwater and Barney (2021) who showed that niche shifts greatly matter when modeling ecological niches of introduced species because they could significantly reduce the transferability of native-and introduced-range ENMs. Additionally, our results suggest the existence of a geographic separation of ranges and ongoing population expansion of M. micrantha in China, while Yang et al (2017) reported genetic differentiation of M. micrantha populations in the IRSWC and IRSC.…”
Section: Implications For Ias Managementsupporting
confidence: 92%
“…Colonization of new regions outside of a species native range induced by human activities is largely linked to shifts in the species realized climatic niches (Atwater et al, 2018). Lacking awareness of niche dynamics of IAS impairs niche‐based predictions of invasion risk assessments (Atwater & Barney, 2021). Understanding niche dynamics of IAS and resulting risk uncertainties is one of the fundamental bases in mitigating invasion impacts and preventing invasions to new environments.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the climatic niches of Ligustrum lucidum W.T.Aiton differed between its invasive and native zones (Dreyer et al, 2019). Furthermore, the climatic niche of 65% out of 815 introduced terrestrial plants was markedly shifted (Zachariah Atwater & Barney, 2021). Taken together, these findings indicate that IAPs may undergo niche shifts upon successfully invading new zones.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, suitable habitat is forecast using the current distribution of a species and associated measured environmental variables (Pearman et al, 2008; Lee‐Yaw et al, 2022). However, meta‐analyses have found that the realized species niches often shift during invasion (Fitzpatrick et al, 2007; Early and Sax, 2014; Atwater et al, 2018; Liu et al, 2020; Atwater and Barney, 2021; Nguyen et al, 2022). Shifts in the realized niche could represent evolution or changes in the available environment (Bates and Bertelsmeier, 2021).…”
mentioning
confidence: 99%
“…In this study, we investigate potential niche shifts during invasion by comparing year‐long and monthly Ecological Niche Models (ENM) in the native and non‐native range of C. bursa‐pastoris . These models are commonly used to study niche differences between native and non‐native populations (Liu et al, 2020; Atwater and Barney, 2021; Nguyen et al, 2022). We use the monthly models to investigate whether change in the timing of the seasonal niche is due to a shift in seasonal timing or a shift in the climatic conditions that predict occurrence.…”
mentioning
confidence: 99%